2021
DOI: 10.3390/biom11121844
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Pseudo-26-kDa Schistosoma Glutathione Transferase from bovis/haematobium for Structure, Kinetics, and Ligandin Studies

Abstract: Glutathione transferases (GSTs) are the main detoxification enzymes in schistosomes. These parasitic enzymes tend to be upregulated during drug treatment, with Schistosoma haematobium being one of the species that mainly affect humans. There is a lack of complete sequence information on the closely related bovis and haematobium 26-kDa GST isoforms in any database. Consequently, we engineered a pseudo-26-kDa S. bovis/haematobium GST (Sbh26GST) to understand structure–function relations and ligandin activity tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Binding of GSH to the active site increases the interactions with the opposing subunit to 15 interactions, while only 8 interactions are found in the apoenzyme [ 42 ]. A similar result was reported for the increase in GST thermal stability in the presence of BSP and GSH [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Binding of GSH to the active site increases the interactions with the opposing subunit to 15 interactions, while only 8 interactions are found in the apoenzyme [ 42 ]. A similar result was reported for the increase in GST thermal stability in the presence of BSP and GSH [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…The low-affinity-binding site(s) for BSP can simultaneously accommodates both BSP and the relatively small size electrophilic substrate, CDNB, and inhibits the enzyme non-competitively [ 39 ]. BSP also inhibits a 26-kDa Schistosoma GST from bovis/haematobium in a noncompetitive manner [ 40 ]. In the present investigation, BSP was found to be a competitive inhibitor for BaGST2 and mixed inhibitor for BaGST3.…”
Section: Discussionmentioning
confidence: 99%
“…S. mansoni GSTs (SmGST) bind and metabolize a diverse array of xenobiotic substances, including drugs, environmental toxins, and plant secondary metabolites. 16 , 17 , 18 Notably, SmGST has limited similarity to human GSTs, thus potentially enabling the development of selective inhibitors that target the parasite while preserving human GST enzymes, and enhancing drug safety. Numerous studies have emphasized the importance of phase I detoxification, and the central roles of glutathione-mediated detoxification and redox metabolism in the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…25,27,31,32 Several compounds have since demonstrated schistosome GST binding, causing varying degrees of enzyme inhibition. Among them are the liver test dye reagent bromosulfophthalein (BSP), 32,33 indanyloxyacetic acid, 32 artemether, 34 the polyphenol ellagic acid, 25 as well as anthraquinone dyes. 35 Much like praziquantel, 22 molecular modeling studies have confirmed the association of these species with non-substrate sites in the binding channel of the enzyme.…”
Section: Introductionmentioning
confidence: 99%